(untitled) (Research, Society and Development, 2023)
Head and neck cancer is a chronic disease considered a public health problem. Among therapeutic modalities, radiotherapy implies oral complications and structural changes in the dental organ, including pulp modifications. In the presence of pulpoperiapical involvement, the atraumatic endodontics is a treatment of choice since it is more conservative and is able to eliminate the infection, avoiding an extraction with potential risk of osteoradionecrosis. In view of this, the objective of this study was to review the literature on the dental surgeons’ conduct with regard to the endodontic treatment in cancer patients irradiated in head and neck. This is an integrative literature review, with qualitative nature and a descriptive approach, carried out between February and August 2022, in Virtual Health Library portal and in the Scientific Electronic Library Online and PubMed databases, using the search strategy “((endodontics AND radiotherapy AND cancer AND treatment) OR (endodontia AND radioterapia AND câncer AND tratamento))”. All of the nine studies included in this research addressed that every patient irradiated in head and neck area that required endodontic treatment in order to eradicate infections and/or prevent extractions, should be treated following the guiding principles of atraumatic endodontics, and so guaranteeing minimum inflammatory tissue reaction. For this, the dental surgeons should have full control of the atraumatic endodontic treatment, providing a more conservative treatment, excellent prognosis and quality of life to such affected individuals.